Evaluation and engineering applications of the in situ stress state of deep tight sandstone reservoirs in the Xujiahe Formation of the Yingshan-Longgang in the central Sichuan Basin - Gao, Songyang; Deng, Hucheng; Yan, Weilin; Yin, Shujun; Zhou, Jiayu; Wen, Zheng; Guo, Yunfei; Zhang, Bo; Li, Chuang; Yang, Xiaolei; Xia, Wenhao; Huang, Tao (Frontiers in Earth Science, 2023)
Introduction: The Xujiahe Formation in the Yingshan-Longgang area of the Sichuan Basin has abundant tight oil and gas resources. However, the complex geological conditions and insufficient understanding of the magnitude and direction of in-situ stresses severely limit exploration and development of oil and gas resources in the region. This has made it difficult to carry out hydraulic fracturing and horizontal well deployment in the region. Methods: Based on experimental analyses, including acoustic emission experiments, wave velocity anisotropy experiments, and paleomagnetic experiments, this study evaluated the magnitude and direction of in-situ stresses, while also combining electrical imaging logging and acoustic wave logging data. This provides a basis for hydraulic fracturing in the research area. Results and Discussion: The experimental results indicate that the three-way stress state of the Xujiahe Formation is a strike-slip stress state, and the three-way stress value gradually increases with increasing burial depth. The Longgang area is particularly affected by the depth. The average azimuth angle of the maximum horizontal principal stress in the study area is N100°E, while tectonic deformation may cause a counterclockwise deviation of the maximum horizontal principal stress azimuth in the Yingshan area. Considering the influence of changes in the magnitude of in situ stress in the longitudinal direction on hydraulic fracturing extension mode, it is recommended to select the middle and upper sections of the Xu II for fracturing and transformation. Similarly, considering the distribution of natural fractures and the direction of the in situ stresses, it is suggested that the deployment azimuth angle for horizontal wells be between N20°–30°E.